Substantial continental temperature rise over the Paleocene-Eocene Thermal Maximum in the Pyrenees - Gábor Újvári; Sándor Kele; László Rinyu; Aitor Payros; Kim H. Stadelmaier; János Kovács; Ivett Kovács; Bernadett Bajnóczi; Victoriano Pujalte; Birger Schmitz; Stefano M. Bernasconi (Communications Earth & Environment)
Abstract The Eocene period experienced several hyperthermal events with the Paleocene-Eocene Thermal Maximum being the most significant. During this event, global mean surface temperatures were 5–6 °C higher and latitudinal temperature gradients were reduced compared to the late Paleocene. Unlike marine temperature records, terrestrial archives are limited, posing challenges for testing climate model competence in simulating the magnitude and spatial patterns of temperature change under a high carbon dioxide climate. Here we analysed mudstone paleosols from the Tremp Group in Spain to reconstruct soil temperatures using carbonate nodules. Clumped isotopes revealed median calcification temperatures of 33.9 and 39.2 °C for the Late Paleocene and Paleocene-Eocene Thermal Maximum, respectively. The findings suggest a ~5 °C summer soil temperature increase during the Paleocene-Eocene Thermal Maximum. Continental proxy and model data indicate reduced (0.7–0.4 °C/degree) meridional temperature gradients between 25 and 75°N latitudes, indicating more uniform heat distribution across latitudes than at present.